Three millennia of vegetation and environmental dynamics in the Lagunas de Mojanda region, northern Ecuador - ANDREA VILLOTA; HERMANN BEHLING; SUSANA LEÓN-YÁNEZ (Acta Palaeobotanica)
The pollen record from Lagunas de Mojanda, located at 3748 m a.s.l. (northern Ecuadorian Andes) reflects the vegetation and climate dynamics for the last ca 3400 cal yr BP. Páramo vegetation has been the main vegetation type since the beginning of the record. At Lagunas de Mojanda, from the last ca 3400 to 2200 cal yr BP, grass páramo was well represented mainly by Poaceae (40%) and the occurrence of Valeriana (5%), while montane forest taxa were poorly represented and subpáramo taxa were rare. The vegetation composition suggests cool and humid conditions. Between ca 2200 and ca 1300 cal yr BP, montane rainforest and subpáramo taxa had a higher presence but páramo taxa remained the main vegetation type in the study area, suggesting cool climatic conditions. From ca 1300 to ca 500 cal yr BP, páramo vegetation remained stable, with higher presence of Phlegmariurus and Isoetes, suggesting cool and humid conditions. The last ca 500 cal yr BP generally show lower frequency of montane rainforest and subpáramo taxa. Páramo vegetation reached the highest share, with the presence of Poaceae, Plantago and Ranunculus suggesting a trend of peat bog drying. Fires were present during the whole record, perhaps human-caused, but the study area does not show great disturbance except from ca 1300 to 500 cal yr BP, a period of an evident higher influx of charcoal particles coincidentally with nearby ancient human occupation.